Dynamic Stability and Trunk Control Improvements Following Robotic Balance and Core Stability Training in Chronic Stroke Survivors: A Pilot Study - De Luca, Alice; Squeri, Valentina; Barone, Laura M.; Vernetti Mansin, Honorè; Ricci, Serena; Pisu, Ivano; Cassiano, Cinzia; Capra, Cristina; Lentino, Carmelo; De Michieli, Lorenzo; Sanfilippo, Carlo A.; Saglia, Jody A.; et al. (Frontiers in Neurology, 2020)
Stroke survivors show greater postural oscillations and altered muscular activation compared to healthy control. This results in difficulties in walking and standing, and in an increased risk of falls. A proper control of the trunk is related to a stable walk and to a lower falling risk; to this extent, rehabilitative protocols are currently working on core stability. The main objective of this work was to evaluate the effectiveness of a trunk and balance training performed with hunova, a new robotic device designed for evaluation and training of balance and core stability, in improving the recovery of chronic stroke patients compared with a traditional physical therapy program. Thirty chronic stroke patients, randomly divided in two groups, either underwent a traditional rehabilitative protocol, or a robot-based program. Each patient was assessed before and after the rehabilitation and at three-months follow-up with clinical and robot-based evaluation exercises focused on static and dynamic balance, core stability and trunk control. Results from clinical scales showed an improvement in both groups in balance and trunk control. Robot-based indices analysis indicated that the experimental group showed greater improvements in proprioceptive control, reactive balance and postural control in unstable conditions, compared to the control group, showing an improved trunk control with reduced compensatory strategies at the end of the training. Moreover, the experimental group had an increased retention of the results obtained with training at three months follow up. These results support the idea that hunova is a promising tool for stroke rehabilitation.